Characterization of neutralizing antibodies reacting with the 213-224 amino-acid segment of human galectin-9. - Claire Lhuillier; Clément Barjon; Valentin Baloche; Toshiro Niki; Aurore Gelin; Rami Mustapha; Laetitia Claër; Sylviane Hoos; Yoichi Chiba; Masaki Ueno; Mitsuomi Hirashima; Ming Wei; et al. (PLoS ONE, 2018)
Extra-cellular galectin-9 (gal-9) is an immuno-modulatory protein with predominant immunosuppressive effects. Inappropriate production of gal-9 has been reported in several human malignancies and viral diseases like nasopharyngeal, pancreatic and renal carcinomas, metastatic melanomas and chronic active viral hepatitis. Therefore therapeutic antibodies neutralizing extra-cellular gal-9 are expected to contribute to immune restoration in these pathological conditions. Two novel monoclonal antibodies targeting gal-9 -Gal-Nab 1 and 2-have been produced and characterized in this study. We report a protective effect of Gal-Nab1 and Gal-Nab2 on the apoptotic cell death induced by gal-9 in primary T cells. In addition, they inhibit late phenotypic changes observed in peripheral T cells that survive gal-9-induced apoptosis. Gal-Nab1 and Gal-Nab2 bind nearly identical, overlapping linear epitopes contained in the 213-224 amino-acid segments of gal-9. Nevertheless, they have some distinct functional characteristics suggesting that their three-dimensional epitopes are distinct. These differences are best demonstrated when gal-9 is applied on Jurkat cells where Gal-Nab1 is less efficient than Gal-Nab2 in the prevention of apoptotic cell death. In addition, Gal-Nab1 stimulates non-lethal phosphatidylserine translocation at the plasma membrane and calcium mobilization triggered by gal-9 in these cells. Both Gal-Nab1 and 2 cross-react with murine gal-9. They bind its natural as well as its recombinant form. This cross-species recognition will be an advantage for their assessment in pre-clinical tumor models.